2021
DOI: 10.3389/fonc.2021.639980
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA LIPE-AS1 Predicts Poor Survival of Cervical Cancer and Promotes Its Proliferation and Migration via Modulating miR-195-5p/MAPK Pathway

Abstract: Aims: A growing number of studies have unveiled that long non-coding RNA (lncRNA) is conductive to cervical cancer (CC) development. However, the effect of LIPE-AS1 is remained to be studied in CC.Main Methods: Reverse transcription-polymerase chain reaction (RT-PCR) was employed to measure LIPE-AS1 expression in CC tissues and the adjacent normal tissues. Additionally, we conducted gain- and loss-of functional experiments of LIPE-AS1 and adopted CCK8 assay, BrdU assay, and in vivo tumor formation experiment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Therefore, it can be speculated that IFNG co-expressed with LINC01871 was associated with promoting cell apoptosis by ferroptosis. As for LIPE-AS1, Zhang et al ( 30 ) reported that overexpression of LIPE-AS1 in cervical cancer can promote cell proliferation, migration, epithelial mesenchymal transition (EMT), and inhibit cell apoptosis, which can be reversed by LIPE-AS1 knockdown or mir-195-5p/mitogen activated protein kinase (MAPK) signaling pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that IFNG co-expressed with LINC01871 was associated with promoting cell apoptosis by ferroptosis. As for LIPE-AS1, Zhang et al ( 30 ) reported that overexpression of LIPE-AS1 in cervical cancer can promote cell proliferation, migration, epithelial mesenchymal transition (EMT), and inhibit cell apoptosis, which can be reversed by LIPE-AS1 knockdown or mir-195-5p/mitogen activated protein kinase (MAPK) signaling pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…HSD17B6 has important functionality in androgen catabolism and was remarkably downregulated in hepatocellular carcinoma, which predicted poor prognosis and high tumor immune infiltrates ( 36 ). It was identified that LIPE is up-regulated in cervical cancer and promotes cell proliferation, invasion, and epithelial-mesenchymal transformation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that lncRNAs may serve as diagnostic and prognostic biomarkers in different types of cancer ( 29 31 ). In addition, certain lncRNAs, such as lncRNA SOX21 antisense divergent transcript 1 ( 32 ) and lncRNA LIPE antisense RNA 1 (LIPE-AS1) ( 33 ), have been indicated to be of use as diagnostic and prognostic biomarkers for patients with CC. The present study also suggested that DLEU1 had the ability to screen patients with CC from normal controls.…”
Section: Discussionmentioning
confidence: 99%